Android-Based Project-Based Learning Integrated Gravimetric Analysis for Chemical Expertise Analysis of Vocational School: Development of Teaching Materials - Hayuni Retno Widarti; Deni Ainur Rokhim; Muchammad Musleh Kadafi (Universitas Islam Indonesia, 2023)
This study aimed to produce gravimetric analysis teaching materials and determine the validity test of gravimetric analysis teaching materials. The development of teaching materials is carried out using the ADDIE development model (Analysis-Design-Development-Implementation-Evaluation). The results of the development of teaching materials are in the form of applications with the APK extension that can be run on Android smartphones. The teaching material validation test obtained the percentage of assessment which included aspects of the content of teaching materials by 84.3% (very feasible), media aspects by 83.9% (very feasible), construct aspects of teaching materials by 81.7% (very feasible), aspects the language used is 79.2% (decent), and the aspect of conformity with the PjBL is 80.9% (very decent). Of the five aspects of the gravimetric analysis validation test assessment, the teaching materials developed were very feasible, with a total percentage of 82.87%. While the readability test got a percentage of 87.3%, so it was categorized as very feasible to use